Interaction studies between calmodulin and gating brake peptides from T-type channels - Yaduvanshi, Shivani; Kumar, Veerendra (Frontiers in Biophysics, 2025)
The voltage gated calcium channels (Cav1 and Cav2) and sodium channels are modulated by calmodulin (CaM) via IQ motifs. But Cav3 (aka T-type) channels lack IQ motif and therefore, they transiently interact with CaM via the gating brake (GB) regions of T-type channels. However, the structural basis of the interactions remains unclear. This study employs molecular dynamics (MD) simulations to investigate the complete binding process of GB peptides (GB3.1 and GB3.2) with CaM at an atomic level, starting from a non-interacting state to a fully formed complex. We provide a detailed analysis of the binding trajectories, identifying how the GB peptides dynamically explore and engage their binding interfaces on CaM. Our results reveal that GB3.1 induces significant conformational rearrangement in CaM, bending its central helix by ∼90° and forming a compact structure. In contrast, GB3.2 binding does not induce such changes, and CaM remains in an extended conformation. Both peptides interact primarily with CaM’s N-lobe. The MM-PBSA analysis yielded negative binding energies indicating a spontaneous and favourable complex formation.